Impact of epidermal growth factor receptor and transforming growth factor–α on hepatitis C virus‐induced hepatocarcinogenesis. Issue 10 (17th August 2015) - Badawy, Afkar Abdel‐Ghany; El‐Hindawi, Ali; Hammam, Olfat; Moussa, Mona; Gabal, Samia; Said, Noha
<x xml:space="preserve">Abstract</x> Epidermal growth factor receptor system plays a central hepato‐protective and pro‐regenerative role in liver. Transforming growth factor‐α (TGF‐α) is an important autocrine growth regulator of hepatocytes that plays a role in development of hepatocellular carcinoma (HCC) among patients with chronic hepatitis C (CHC). This study was done on 40 core liver biopsies from patients with CHC, 20 liver specimens from HCC cases on top of CHC as well as five normal controls. All were immunohistochemically stained with epidermal growth factor receptor (EGFR) and TGF‐α antibodies. Some selected HCC cases were submitted for FISH technique to detect EGFR gene alteration. By immunohistochemistry EGFR and TGF‐α were overexpressed in HCC and cirrhotic cases compared to CHC cases without cirrhosis. Also, their expression was stronger in CHC cases with higher grades of activity and stages of fibrosis compared to lower ones. FISH positive results for EGFR were detected in 33.3% of the examined HCC cases. EGFR and TGF‐α can be used as predictive markers for activity, fibrosis, and carcinogenesis in CHC patients. Overexpression of EGFR in HCC patients can be promising in selecting those who can get benefit from anti‐EGFR target therapy.